2014
DOI: 10.1063/1.4890104
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal single particle microscopy using a single laser beam

Abstract: We introduce a single-laser-beam photothermal microscopy scheme for the detection of single absorbing nano-objects. Here, a modulated incident laser beam with a constant intensity offset serves as pump and probe beam at the same time. Using the out-of-phase scattering response of the retarded thermorefractive wave field, the method provides a selective contrast for absorbers over a possible background of scatterers. The use of a single wavelength and a single beam, considerably simplifies the setup and integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…21 Indirect detection schemes combined with modulation techniques have been developed for absorption-based detection, [22][23][24][25] 4 including ground-state depletion microscopy 15,26 and photothermal microscopy. 11,13,14,16,[27][28][29][30] However, most studies using these methods have reported single-wavelength imaging without yielding spectroscopic information. A tunable dye laser, incorporated as the excitation source into a photothermal microscope, has allowed the acquisition of absorption, albeit in a limited spectral range of 515 nm to 585 nm, for which chromatic aberrations were mostly negligible.…”
mentioning
confidence: 99%
“…21 Indirect detection schemes combined with modulation techniques have been developed for absorption-based detection, [22][23][24][25] 4 including ground-state depletion microscopy 15,26 and photothermal microscopy. 11,13,14,16,[27][28][29][30] However, most studies using these methods have reported single-wavelength imaging without yielding spectroscopic information. A tunable dye laser, incorporated as the excitation source into a photothermal microscope, has allowed the acquisition of absorption, albeit in a limited spectral range of 515 nm to 585 nm, for which chromatic aberrations were mostly negligible.…”
mentioning
confidence: 99%
“…(4) for radii larger than the particle radius R 5 λ. This is the situation commonly encountered in photothermal single particle microscopy [4][5][6][7][8][9]. Using Eq.…”
Section: The 1/r Refractive Perturbationmentioning
confidence: 98%
“…In particle scattering, the latter form may be taken to represent the electronic shielding of the nuclear charge which limits the range of its Coulomb potential. Similarly, the optical inhomogeneity in photothermal microscopy does not extend indefinitely under realistic conditions [9]. In heterodyne photothermal microscopy, an exponential damping is determined by the thermal diffusivity of the embedding medium and the modulation frequency of heating of the absorbing nanoparticle [4,9].…”
Section: The 1/r Refractive Perturbationmentioning
confidence: 99%
See 1 more Smart Citation
“…In stimulated emission and stimulated Raman microscopy, the intensity of the pump beam is modulated at high frequency (>1 MHz) because the laser intensity noise of a solid state laser used for probing occurs primarily at low frequencies (from kilohertz to DC) in the form of 1/f noise [14,23,24]. However, in PT microscopy, the high-frequency modulation scheme reduces signal intensity because the time response of the PT signal is, in principle, determined by heat conductivity and is decreased by half at~1 MHz for a tightly focused laser beam [25][26][27][28]. Moreover, the high-frequency modulation scheme cannot circumvent the high-frequency laser noise that usually presents in the laser diodes and amplified fiber lasers.…”
Section: Improvement In Snr By the Spatially Segmented Balanced Detecmentioning
confidence: 99%